Intelligent technology and engineering practice of backfilling mining in Xingdong Mine - ZHANG Jianzhong; WANG Yunbo; YANG Junhui; YANG Yinchao; WU Honglin; CHEN Feng; ZHANG Jian (Gong-kuang zidonghua, 2023)
Intelligent backfilling mining meets the industry development trend and need of green and intelligent mining in coal mines. But there is currently a lack of systematic research and practical engineering applications on key technologies of intelligent backfilling mining. In order to solve this problem, with the core of intelligent upgrading of solid backfilling mining faces, the primary goal of intelligent control of backfilling rate, and the goal of building intelligent backfilling mines, the key technologies of intelligent backfilling mining are systematically studied. The technologies include intelligent pretreatment and delivery control technology for coal-based solid waste, the underground intelligent jigging separation technology combined with real-time monitoring and control of ore deposits, intelligent control of waste discharge speed, and mixed separation control, the multi-source coal-based solid waste collection, storage and transportation technology based on real-time monitoring and precise feedback control of multi-source coal-based solid waste, and the intelligent solid backfilling and mining technology which integrates intelligent backfilling monitoring, intelligent flow control, backfilling hydraulic support, and electrohydraulic control of the working face. Through the linkage and coordination of various key intelligent backfilling mining technologies, Xingdong Mine has formed an intelligent backfilling mine with coal-based solid waste pretreatment, underground coal gangue separation, multi-source coal-based solid waste storage and transportation, and solid backfilling mining as the core. The results of engineering practice show that the capacity of intelligent backfilling working faces has been greatly improved after the application of intelligent backfilling mining technology. The working faces' output increases from 36000 t per month to 72000 t per month. The number of personnel per shift is reduced by 8-10. The time of one cycle operation is reduced by about 2.5 h, and the efficiency increases by about 50%. The problem of coal-based solid waste discharge has been comprehensively solved.